Past and Future: The Temporal Dimension in the Law of Property - Richard A. Epstein (Washington University Law Quarterly, 1986)
This Article deals with time in two separate senses. In one sense, it is about how the categorical nature of time, as a necessary element of human experience and comprehension, shapes substantive and procedural legal rules. In a second sense, however, the larger part of this Article focuses on the contingent nature of time, that is, about the length of interval between cause and effect, between antecedent and consequence. The central theme of the Article is simple. The major cost associated with the passage of time is uncertainty. For risk averse individuals, that uncertainty creates a cost that greater certainty could reduce. In addition, any increase of uncertainty increases the scope of the discretion lodged in both public and private hands. That discretion spurs private litigation that generates high administrative costs and high error rates. The passage of time therefore creates pressures, both public and private, to take steps to ensure that legal rights and duties do not depend on events that are remote from the present, either past or future. These practical demands often clash with the strict principles of corrective justice, where the passage of time is of no particular consequence in determining the relative rights and duties of all persons. As an abstract principle each violation of individual rights appears to require full redress on a case by case basis. The ungainly structure of legal doctrine is sometimes explained by the difficult task of reconciling these two inconsistent tendencies in a wide range of specific contexts.